1998
DOI: 10.1016/s0960-9822(98)70467-1
|View full text |Cite
|
Sign up to set email alerts
|

The Ras recruitment system, a novel approach to the study of protein–protein interactions

Abstract: The yeast two-hybrid system represents one of the most efficient approaches currently available for identifying and characterizing protein-protein interactions [1-4]. Although very powerful, this procedure exhibits several problems and inherent limitations [5]. A new system, the Sos recruitment system (SRS), was developed recently [6] based on a different readout from that of the two-hybrid system [6-8]. SRS overcomes several of the limitations of the two-hybrid system and thus serves as an attractive alternat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
167
1
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(170 citation statements)
references
References 22 publications
1
167
1
1
Order By: Relevance
“…We and others reported that JDP2 is an AP-1 transcriptional repressor 15,[17][18][19][20] with histone-chaperone activity that inhibits histone acetylation by recruiting HDAC3. 24 JDP2 also inhibited the RA-dependent differentiation of embryonic carcinoma F9 cells.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…We and others reported that JDP2 is an AP-1 transcriptional repressor 15,[17][18][19][20] with histone-chaperone activity that inhibits histone acetylation by recruiting HDAC3. 24 JDP2 also inhibited the RA-dependent differentiation of embryonic carcinoma F9 cells.…”
Section: Discussionmentioning
confidence: 90%
“…12,13 Jun dimerization protein 2 (JDP2) is a DNA-binding protein that forms homodimers or heterodimers with c-Jun, ATF2 and C/EBPg. [14][15][16] JDP2 can function not only as a transcriptional repressor but also as a coactivator in various types of cell, 15,[17][18][19][20] and it is involved in a variety of biological phenomena such as proliferation and differentiation of cells and apoptosis. 14,15,17,18,[20][21][22] For example, forced expression of JDP2 represses the retinoic acid-mediated (RA-mediated) transcription of the c-jun gene and the differentiation of F9 cells in response to RA.…”
mentioning
confidence: 99%
“…Recently, two novel protein-protein interaction assays were developed which complement and overcome some of the problems and limitations of the two hybrid system (11,12). These assays are based on a completely different readout to monitor a successful protein-protein interaction in yeast.…”
Section: Introductionmentioning
confidence: 99%
“…These assays are based on a completely different readout to monitor a successful protein-protein interaction in yeast. It is based on translocation of the active molecules, hSos (11) or Ras (12) to their site of action at the inner leaflet of the plasma membrane. Translocation is achieved through protein-protein interaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation